Bimetal Catalysts: Bimetal Schottky Heterojunction Boosting Energy‐Saving Hydrogen Production from Alkaline Water via Urea Electrocatalysis (Adv. Funct. Mater. 21/2020). (20th May 2020) - Wang, Chao; Lu, Haoliang; Mao, Zeyang; Yan, Chenglin; Shen, Guozhen; Wang, Xianfu
Abstract : In article number 2000556, Chenglin Yan, Guozhen Shen, Xianfu Wang, and co‐workers present a bimetal Schottky heterojunction using an in‐situ electrochemical turning strategy. With the self‐driven charge transfer and redistribution at the interface, the developed catalyst with its built‐in electric field demonstrates excellent bifunctional catalysis for both urea oxidation and hydrogen evolution in alkaline systems.